Perubahan peran dan fungsi benteng dalam tata ruang kota - Marihandono, Djoko (UI Scholars Hub, 2008)
This research aims to explain and describe the colonial history of fortresses and their influence on the development of urban planning in Indonesia. The fortresses functioned as centres of colonial administration and control. In former days these fortresses were identified with the domination of power, economic exploitation and as symbols of foreign rule in areas ruled by local kings and entrepeneurs. Due to political and economic changes as well as in town planning, the funtion of these fortresses also changed. At present, the fortresses function as heritage sites and interesting places to be visited by tourists. The current efforts to conserve these historical sites can have an effect on urban development planning. The Indonesian government, especially the Department of Tourism and Culture, should give much attention not only for preservation but also for restauration of these sites.